Financing Basie Education in Nigeria: Linking Resources to Learning Outcomes - Thecla, Amogechukwu Eze (International Journal of Educational Management, 2025)
Basic education represents the very first level of education a child is exposed to. I is compulsory and universal. The financing, though complex comes mainly from the Federal Government block grant of not less than 2% of its Consolidated Revenue Funds. Generally, the budget for education fall short of international recommendations. This affects provisions considerably, which invariably affects the learning outcomes of the children. Review of the current funding status is needed.